Increase in serum Interleukin-10 does not alleviate pro-inflammatory MCP-1 production in obese pregnancies. (August 2018) - Polari, Lauri; Kumar, Himanshu; Rautava, Samuli; Salminen, Seppo; Isolauri, Erika
Highlights: Circulating cytokine concentrations change from 1st to 3rd trimester of pregnancy. Proportion of anti-inflammatory skew depends on inflammatory status at 1st trimester. Pre-pregnancy obesity (BMI > 30) disrupts gestational down-regulation of MCP-1. Abstract: Maternal cytokine profiles during pregnancy are characterized by significant deviations, varying substantially between gestational time points and tissues. Obesity, in turn, is linked with low-grade inflammation in adipose tissue and increased concentrations of systemic inflammatory mediators. However, the balance of pro- and anti-inflammatory cytokines in obese pregnancy has remained elusive. In view of the demonstrations that the obesity is a global epidemic in the population at reproductive age with a strong intergenerational impact, we investigated the relation of gestational immune adaptations and obesity-induced inflammation. We found a significant decrease in systemic IL-1β and MCP-1 concentration from 1st to 3rd trimester of pregnancy while IL-10 concentration increased, respectively. However, in obese pregnancies this reduction of pro-inflammatory mediators was not detected. This may constitute an additional risk factor in obese pregnancies in which the concentration of MCP-1 is already upregulated compared to normal weight mothers.